2019
DOI: 10.1007/s42452-019-1637-3
|View full text |Cite
|
Sign up to set email alerts
|

Control of the buoyancy of Microcystis aeruginosa via colony formation induced by regulating extracellular polysaccharides and cationic ions

Abstract: It is well recognized that gas vesicles influence the buoyancy of Microcystis and control the migration in the water column. Some of Microcystis strains do not have gas vesicles, so these strains cannot obtain buoyancy from them. In this study, we used two types of Microcystis strains such as the non-gas vesicle synthesizing strain M. aeruginosa UTEX-2061 and the gas vesicle synthesizing strain M. aeruginosa NIES-843 in the buoyancy control experiments of M. aeruginosa. By inducing colony formation and calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The aggregation prolongs Microcystis in water bodies and enhances buoyancy ( Drugǎ et al, 2019 ). At a laboratory scale, an aggregated form of SG03 was initiated by calcium addition ( Drugǎ et al, 2019 ; Wei et al, 2019 ; Gu et al, 2020 ). The aggregated cells were infected by cyanophage PhiMa05 at different MOIs of 0.1, 1, 10, and 100.…”
Section: Resultsmentioning
confidence: 99%
“…The aggregation prolongs Microcystis in water bodies and enhances buoyancy ( Drugǎ et al, 2019 ). At a laboratory scale, an aggregated form of SG03 was initiated by calcium addition ( Drugǎ et al, 2019 ; Wei et al, 2019 ; Gu et al, 2020 ). The aggregated cells were infected by cyanophage PhiMa05 at different MOIs of 0.1, 1, 10, and 100.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, recent studies suggested that extracellular polysaccharides are also important for the bloom formation ( Chen et al, 2019 ). Some papers reported that the cells without gas vesicle can form blooms by EPS-dependent manner after artificial addition of divalent cations (Ca 2+ or Mg 2+ ) ( Dervaux et al, 2015 ; Wei et al, 2019 ). On the other hand, our study demonstrated that the gas-trapped EPS is sufficient for bloom formation of Synechocystis 6803, which does not produce gas vesicles, without addition of any divalent cations ( Figure 4B ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent studies suggested that extracellular polysaccharides are also important for the bloom formation ( Chen et al, 2019 ). Some papers reported that the cells without gas vesicle can form blooms by EPS-dependent manner after artificial addition of divalent cations (Ca 2+ or Mg 2+ ) ( Dervaux et al, 2015, Wei et al, 2019 ). On the other hand, our study demonstrated that the gas-trapped EPS is sufficient for bloom formation of Synechocystis 6803, which does not produce gas vesicles, without addition of any divalent cations.…”
Section: Discussionmentioning
confidence: 99%